A bio-oil hydrodeoxygenation catalyst and its preparation method and application
By using MXenes material as a carrier, the hydrodeoxygenation catalyst of bio-oil hydrodeoxygenation, combined with hydrogenation active metal and additive metal, the existing catalyst activity and stability are solved, and efficient hydrodeoxygenation reaction and environmentally friendly industrial application are achieved. .
Patent Information
- Application Number
- CN202411245313.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-06
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2044-09-06
AI Technical Summary
The activity and stability of existing bio-oil hydrodeoxygenation catalysts are relatively low, the preparation process is complicated and not conducive to industrial application.
Using catalysts including hydrogenation active metal, hydrogenation additive metal and MXenes (two-dimensional transition metal carbon/nitride) materials, MXenes carriers are prepared by fluoride hydrochloric acid solution etching method, combining hydrogenation active metal and additive metal precursors The immersion and calcination steps of the body form an efficient hydrodeoxygenation catalyst for bio-greasing and fat.
The catalyst has high hydrogenation performance and reaction stability, avoids sulfur residue and environmental pollution, simplifies the preparation process, and is suitable for industrial applications.
Smart Images

Figure CN118831620B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of biomass resource utilization, and specifically relates to a bio-oil hydrodeoxygenation catalyst and a preparation method and application thereof. Background Art
[0002] With the continuous development of industrialization, the demand for fossil fuels around the world is still high, resulting in the increasing shortage of non-renewable resources. The use of fossil fuels will cause environmental pollution, biodiversity loss, global warming and climate disasters, etc. Therefore, the development of green and environmentally friendly renewable energy has become an important issue that needs to be urgently addressed. Bio-oils (such as animal and plant fats, waste oils) are considered to be a sustainable renewable resource due to their good environmental performance, wide sources and low prices. However, due to their high oxygen content and high unsaturation, bio-oils have low quality, high acid value, poor thermal stability and easy corrosion of reaction equipment, so bio-oils need to be improved. Hydrodeoxygenation technology can reduce the content of oxygen-containing compounds in bio-oils and reduce unsaturated bonds in the molecular structure, thereby improving their chemical properties and antioxidant capacity, and reducing viscosity and acid value.
[0003] In the bio-oil hydrodeoxygenation technology, the preparation of catalysts with high catalytic activity, high selectivity and good stability is the key. Precious metal catalysts have excellent hydrogenation performance and mild reaction conditions, but they are expensive and costly, which is not conducive to large-scale industrial application. Metal sulfide catalysts have rich electronic structures and chemical bond properties and show good activity in hydrodeoxygenation, but the activity of sulfide catalysts decreases due to the loss of sulfur, and residual sulfur is left in the hydrogenation product, which not only leads to a decrease in the quality of downstream oil products, but also easily causes environmental pollution. Reduced non-precious metals have strong adsorption and activation capabilities for hydrogen and are low in cost. Using non-precious metals instead of precious metals for catalytic hydrodeoxygenation of bio-oils has become a research hotspot in this field.
[0004] Chinese patent CN 115138370B discloses a bio-oil hydrodeoxygenation catalyst, which contains Ni as the main catalytic active metal, W / Mo as the co-catalytic active metal, rare earth elements as the catalyst promoter, and spinel structure alumina as the carrier. In a trickle bed reactor, the preferred catalyst exhibits a high soybean oil conversion rate and nC 15 ~nC 18 However, the preparation process of the catalyst needs to be strictly controlled, which is not conducive to industrial application.
[0005] Chinese patent CN 110465314A discloses a bimetallic phosphide hydrodeoxygenation catalyst. When the reaction temperature is 335 °C, the conversion rate of soybean oil methyl ester is 99.1%. 15-18The alkane yield reached 87.1%, but the introduction of precious metal Pd increased the catalyst preparation cost. At the same time, the water molecules generated during the hydrodeoxygenation process easily converted the carrier alumina into hydrated alumina, causing the catalyst stability to decrease.
[0006] Chinese patent CN 116726936A discloses a non-precious metal M@SiO2 core-shell structure oil hydrodeoxygenation catalyst, which is made by a coating method with non-precious metals such as Cu, Co, and Ni as the inner shell and SiO2 as the outer shell. In the hydrodeoxygenation reaction of methyl palmitate, the obtained catalyst exhibits good catalytic performance. However, the preparation process of the catalyst is relatively complicated and it is difficult to promote and apply it industrially.
[0007] Bio-oils are mainly composed of a large number of fatty acid glycerides (triglycerides) and a small amount of free fatty acids. The chain lengths of fatty acid glycerides vary greatly, with single chains containing 16, 18 and 20 carbon atoms being the most common. The molecular molar mass of the triglyceride molecules formed can reach about 1000, and the molecular size is relatively large. During the hydrodeoxygenation reaction, the diffusion steric hindrance of fatty acid glycerides on the hydrodeoxygenation catalyst is relatively large, resulting in an increase in their residence time on the hydrogenation active metal sites, which can easily cause side reactions such as decarboxylation and decarbonization, resulting in a decrease in carbon atom utilization; at the same time, the generated water molecules will oxidize the hydrogenation active metals and corrode the carrier, causing the catalyst activity to decrease and the stability to deteriorate. Summary of the invention
[0008] The object of the present invention is to provide a bio-oil hydrodeoxygenation catalyst, a preparation method and an application thereof, and to solve the problems of low activity and stability of the bio-oil hydrodeoxygenation catalyst in the prior art. A bio-oil hydrodeoxygenation catalyst, a preparation method and an application thereof are provided. The method is simple, the conditions are mild, and it is easy to control. The prepared catalyst exhibits excellent hydrogenation performance and reaction stability.
[0009] A bio-oil hydrodeoxygenation catalyst comprises a hydrogenation active metal, a hydrogenation auxiliary metal and a MXenes (two-dimensional transition metal carbon / nitride) material carrier; the hydrogenation active metal, calculated as oxide, accounts for 15-30% of the total mass of the bio-oil hydrodeoxygenation catalyst; the hydrogenation auxiliary metal, calculated as oxide, accounts for 5-20% of the total mass of the bio-oil hydrodeoxygenation catalyst. The MXenes carrier component accounts for 50-80% of the total mass of the catalyst.
[0010] Preferably, the MXenes material carrier is selected from Ti3C2T x 、Ti2CT x 、Nb2CT x 、Nb4C3T x 、Mo3C2T x One or more of .
[0011] Preferably, the MXenes material carrier is Ti3C2T x -Nb2CT x 、Ti3C2T x -Nb4C3T x 、Ti3C2T x -Mo3C2T x 、Ti2CT x -Nb2CT x 、Ti2CT x -Nb4C3T x 、Ti2CT x -Mo3C2T x 、Nb2CT x -Mo3C2T x 、Nb4C3T x -Mo3C2T x 、Ti3C2T x -Mo3C2T x -Nb2CT x 、Ti3C2T x -Mo3C2T x -Nb4C3T x 、Ti2CT x -Nb2CT x -Mo3C2T x 、Ti2CT x -Nb4C3T x -Mo3C2T x One or more of the following. Two MXenes composite supports (CD), component C accounts for 30-50% of the total mass of the catalyst, and component D accounts for 20-30% of the total mass of the catalyst; three MXenes composite supports (EFG), component E accounts for 30-40% of the total mass of the catalyst, component F accounts for 10-20% of the total mass of the catalyst; component G accounts for 10-20% of the total mass of the catalyst.
[0012] Preferably, the MXenes material carrier is Ti3C2T x -Mo3C2T x -Nb4C3T x Composite, Ti3C2T x 、Mo3C2T x 、Nb4C3T x The mass ratio is 6:4:3.
[0013] Preferably, the hydrogenation active metal is one or two of Co and Ni; the hydrogenation promoter metal is one or more of Mo, W, Fe and Cu.
[0014] The preparation method of the above-mentioned bio-oil hydrodeoxygenation catalyst comprises the following steps:
[0015] (1) Slowly adding MAX powder to a hydrochloric acid solution of a fluorine-containing compound, wherein the molar ratio of MAX to fluoride ion is 1:7-1:30 (preferably 1:7-1:25); etching at a speed of 200-1200 rpm and a temperature of 0-60 °C for 2-72 h;
[0016] (2) After solid-liquid separation, the solid was washed with deionized water until the pH was greater than 6, and the solid precipitate was vacuum dried at 55-100 °C for 12-48 h to obtain a MXenes material carrier;
[0017] (3) Supersaturated or equal volumes of hydrogenation active metal precursor and auxiliary metal precursor are impregnated into the MXenes material carrier obtained in step (2), and dried at 50-200 °C for 2-40 h; more preferably, the drying temperature is 50-180 °C and the drying time is 6-40 h.
[0018] (4) Then, the mixture is calcined at a temperature of 300 to 800°C for 2 to 48 hours. A more preferred calcination temperature is 300 to 750°C and the calcination time is 4 to 48 hours.
[0019] The present invention adopts fluoride hydrochloric acid solution etching, the preparation method is safer and simpler, the reaction conditions are milder and more controllable, HF is released slowly, and less fluoride ions remain, thereby obtaining a more uniform MXenes material with a larger interlayer spacing and higher purity.
[0020] The MXenes material carrier of the present invention is obtained by the MAX liquid phase etching method, and has the characteristics of stable chemical properties, large specific surface area, rich surface groups, etc. It can promote the high dispersion of active metal components and auxiliary metal components, and is beneficial to the full contact of macromolecular reactants with hydrogenation active sites and the rapid diffusion of generated water.
[0021] Preferably, the fluorine compound includes one or more of lithium fluoride, sodium fluoride, potassium fluoride, and ammonium fluoride; and the concentration of the hydrochloric acid is 6-15 mol / L.
[0022] The mass ratio of MAX to deionized water in the liquid phase etching method is 1:5-1:40, preferably, the mass ratio is 1:5-1:35.
[0023] The MAX precursor is any one or more of Ti3AlC2, Ti2AlC, Ti2AlN, Nb2AlC, Nb4AlC3, Mo3AlC2, Mo2Ga2C, Cr2AlC, Ta4AlC3, Ta2GaC, V3AlC2, and V2AlC. Preferably, the MAX precursor is any one or more of Ti3AlC2, Ti2AlC, Nb2AlC, Nb4AlC3, and Mo3AlC2.
[0024] Preferably, the hydrogenation active metal precursor includes one or more of nickel nitrate, nickel carbonate, basic nickel carbonate, nickel oxalate, nickel formate, nickel acetate, nickel phosphate, nickel citrate, nickel sulfate, cobalt nitrate, basic cobalt carbonate, and cobalt acetate; the auxiliary agent metal precursor includes one or more of ammonium molybdate, ammonium paramolybdate, ammonium phosphomolybdate, ammonium tungstate, ammonium metatungstate, ammonium paratungstate, ammonium phosphotungstate, copper nitrate, copper chloride, copper citrate, copper acetate, iron formate, iron tartrate, ferric chloride, ferrous chloride, and ferric nitrate.
[0025] The above bio-oil hydrodeoxygenation catalyst is used for the hydrodeoxygenation reaction of model compounds or bio-oil.
[0026] The method of using the bio-oil hydrodeoxygenation catalyst for hydrodeoxygenation reaction comprises taking a model compound or biomass oil as a raw material, reducing it at 200-550°C for 2-12 h in a hydrogen atmosphere, wherein the reduction pressure is normal pressure to 3.0 MPa, and the gas space velocity is 1000-10000 h -1 The bio-oil hydrodeoxygenation catalyst is placed in a fixed bed reactor to perform a hydrodeoxygenation reaction.
[0027] Preferably, the reaction temperature is 200-500°C, more preferably 260-500°C, the reaction pressure is 1-12 MPa, more preferably 2-10 MPa, and the gas space velocity is 500-4000 h -1 , more preferably 1000~3000 h -1 , the hydrogen / oil volume ratio is 200~5000, and more preferably 500~5000.
[0028] The catalyst of the present invention is applied to the hydrodeoxygenation reaction of model compounds or bio-oils, with mild conditions, high raw material conversion rate and normal hydrocarbon product selectivity, good stability, and the quality of bio-oils is improved, laying a foundation for its further application.
[0029] The catalyst provided by the present invention can be applied to the reaction of preparing alkanes by hydrodeoxygenation of biological oil model compounds and real oil products. Preferably, the biological oil model compound is selected from one or a mixture of myristic acid, palmitic acid, stearic acid, oleic acid, linoleic acid, and linolenic acid; preferably, the real oil product is selected from one or a mixture of soybean oil, palm oil, rapeseed oil, cottonseed oil, peanut oil, sesame oil, castor oil, and waste oil.
[0030] MXenes are a new type of two-dimensional transition metal carbon / nitrogen compounds with a layered structure, and their composition can be expressed as M n+1 X n T x (M represents a transition metal, X is C and / or N, T x is a functional group such as OH, O, F, and n is generally 1-3), because of its unique physical and chemical properties, high specific surface area, excellent mechanical properties, good chemical stability and environmental friendliness, it can be used as a high-quality carrier for hydrogenation deoxygenation catalytic reactions. The present invention uses MXenes layered carriers to achieve high dispersion of hydrogenation active metals, on the one hand, improve the diffusion behavior of fatty acid glycerides, promote their rapid conversion at hydrogenation active sites, increase hydrogenation depth, and inhibit side reactions. On the other hand, it avoids the corrosion of the catalyst structure by the generated water and increases the hydrogenation stability of the catalyst.
[0031] Compared with the prior art using a sulfurized bio-oil hydrodeoxygenation catalyst, the catalyst provided by the present invention does not require presulfurization and intermediate sulfur supplementation, and achieves sulfur-free operation throughout the entire process, which can not only avoid sulfur residue in downstream products, but also avoid poisoning of downstream hydrodeoxygenation catalysts and reduction in product quality; the gas product can be directly recycled after decarbonization, which can reduce the investment in desulfurization equipment; in addition, no sulfur-containing waste gas and solid waste are generated, the environmental pollution is small, and it has excellent social and economic benefits.
[0032] Compared with the non-sulfurized bio-oil hydrodeoxygenation catalyst used in the prior art, the catalyst provided by the present invention uses MXenes materials with a two-dimensional layered structure as a carrier, which is conducive to the high dispersion of hydrogenation active metals and their mutual combination with hydrogenation auxiliary metals, providing more active sites for the hydrogenation process of oil molecules; moreover, its structure is conducive to improving the diffusion behavior of reactant molecules, intermediates and products, and the obtained catalyst exhibits a higher hydrogenation depth and better hydrogenation selectivity, inhibits the occurrence of side reactions such as decarboxylation, decarbonylation, and hydrogenolysis, and achieves the purpose of achieving high hydrodeoxygenation catalytic activity and selectivity under mild reaction conditions. At the same time, the two-dimensional layered structure can accelerate the diffusion and removal of generated water, preventing it from staying on the hydrogenation metal site for a long time and causing oxidation. Therefore, the obtained catalyst can show excellent stability in the hydrodeoxygenation reaction process of model compounds and real oil products, showing good application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 For Ti2AlC and Ti2CT in Example 1 x XRD spectrum of
[0034] Figure 2 For Ti3AlC2 and Ti3C2T in Example 2 x XRD spectrum of
[0035] Figure 3 Nb2AlC and Nb2CT in Example 3 x XRD spectrum of
[0036] Figure 4 Nb4AlC3 and Nb4C3T in Example 6 x XRD spectrum of
[0037] Figure 5 Ti3C2T prepared in Example 2 x SEM images of
[0038] Figure 6 Nb4C3T prepared in Example 6 x -Mo3C2T x SEM image of the composite carrier;
[0039] Figure 7 Ti3C2T prepared in Example 8 x -Mo3C2T x -Nb4C3T x SEM image of the composite carrier;
[0040] Figure 8 GC spectra of the product (b) of the stearic acid hydrodeoxygenation reaction catalyzed by the catalyst A8 obtained in Example 8 and the raw material stearic acid (a);
[0041] Fig. 9 The stability test results of the catalyst A8 obtained in Example 8 when cottonseed oil is used as the raw material. DETAILED DESCRIPTION
[0042] In order to make the objectives, technical solutions and advantages of the present invention more clear, the present invention will be further described in detail below with reference to the accompanying drawings.
[0043] Example 1
[0044] Preparation of a highly efficient reduced metal / MXenes catalyst for hydrodeoxygenation
[0045] (1) 3 g Ti2AlC powder was slowly added to a mixed solution of 9.5 g sodium fluoride and 80 mL hydrochloric acid (6 mol / L), and treated at 45 °C for 36 h under magnetic stirring at 700 rpm. After the treatment, the solid product was washed with deionized water by high-speed centrifugation (5000 rpm, 5 min) until the pH value of the upper liquid was higher than 6. The solid precipitated product was collected, transferred to a vacuum drying oven, and dried at 65 °C for 24 h to obtain Ti2CT. x Material carrier.
[0046] (2) Weigh 1.94 g of cobalt nitrate and 3.24 g of nickel nitrate, dissolve them in deionized water to prepare a mixed aqueous solution, and immerse an equal volume of the mixed solution into the 2 g Ti2CT x After impregnation on the support for 20 h, it was transferred to a vacuum drying oven and dried at 120 °C for 14 h, and then calcined at 550 °C in a muffle furnace for 6 h to obtain catalyst A1.
[0047] Example 2
[0048] (1) 3 g Ti3AlC2 powder was slowly added to a mixed solution of 6.3 g lithium fluoride and 60 mL hydrochloric acid (9 mol / L), and treated at 35 °C for 36 h under magnetic stirring at 550 rpm. After the treatment, the solid product was washed with deionized water by high-speed centrifugation (5000 rpm, 5 min) until the pH value of the upper liquid was higher than 6. The solid precipitated product was collected, transferred to a vacuum drying oven, and dried at 60 °C for 24 h to obtain Ti3C2T x Material carrier.
[0049] (2) Weigh 0.45 g of ammonium molybdate and dissolve it in deionized water to prepare an aqueous solution, and immerse an equal volume of the solution into the 2 g Ti3C2T x The catalyst precursor was obtained by impregnating the carrier for 10 h, transferring it to a vacuum drying oven, and drying it at 130 °C for 8 h to obtain a catalyst precursor, denoted as K1. 0.69 g of basic cobalt carbonate and 0.79 g of nickel carbonate were weighed and dissolved in deionized water to prepare a mixed aqueous solution, and an equal volume of the solution was impregnated on K1. After impregnation for 15 h, the catalyst precursor was transferred to a vacuum drying oven, dried at 100 °C for 10 h, and then calcined in a muffle furnace at 600 °C for 6 h to obtain catalyst A2.
[0050] Depend on Figure 5 It can be seen that the Ti3C2Tx material obtained in Example 2 has an accordion-like morphology.
[0051] Example 3
[0052] (1) 2 g Nb2AlC powder was slowly added to a mixed solution of 5.4 g potassium fluoride and 50 mL hydrochloric acid (10 mol / L), and treated at 40 °C for 36 h under magnetic stirring at 560 rpm. After the treatment, the solid product was washed with deionized water by high-speed centrifugation (5500 rpm, 6 min) until the pH value of the upper liquid was higher than 6. The solid precipitated product was collected, transferred to a vacuum drying oven, and dried at 85 °C for 36 h to obtain Nb2CT. x The Ti2CT obtained in step (1) of Example 1 was mechanically mixed. x Materials and Nb2CT obtained in this step x Materials composite (Ti2CT x :Nb2CT x =3:2 mass ratio), to obtain a catalyst carrier, recorded as B1.
[0053] (2) Weigh 3.50 g of cobalt nitrate and 2.01 g of basic nickel carbonate, dissolve them in deionized water to prepare a mixed aqueous solution, supersaturate impregnate 3 g of B1, impregnate for 28 h, filter out the excess solution, transfer it to a vacuum drying oven, and dry it at 110 °C for 14 h to obtain a catalyst precursor, recorded as K2; weigh 2.73 g of copper nitrate, dissolve it in deionized water to prepare an aqueous solution, supersaturate impregnate K2, impregnate for 25 h, filter out the excess solution, transfer it to a vacuum drying oven, dry it at 120 °C for 10 h, and then calcine it in a muffle furnace at 550 °C for 8 h to obtain catalyst A3.
[0054] Example 4
[0055] (1) The Ti3C2T3O4 obtained in step (1) of Example 2 was mixed by mechanical mixing. x Materials and Nb2CT obtained in step (1) of Example 3 x Materials are composited (Ti3C2T x :Nb2CT x =2:1 mass ratio), to obtain a catalyst carrier, denoted as B2.
[0056] (2) Weigh 5.19 g of nickel nitrate, dissolve it in deionized water to prepare an aqueous solution, impregnate it onto 4 g of B2 in an oversaturated manner, filter out the excess solution after impregnation for 18 h, transfer it to a vacuum drying oven, and dry it at 140 °C for 12 h to obtain a catalyst precursor, recorded as K3; weigh 2.93 g of ammonium tungstate, dissolve it in deionized water to prepare an aqueous solution, impregnate an equal volume of K3, impregnate it for 16 h, transfer it to a vacuum drying oven, dry it at 100 °C for 10 h, and then calcine it in a muffle furnace at 550 °C for 8 h to obtain catalyst A4.
[0057] Example 5
[0058] (1) 2 g of Mo3AlC2 powder was slowly added to a mixed solution of 3.9 g of lithium fluoride and 75 mL of hydrochloric acid (12 mol / L), and treated at 50 °C for 44 h under magnetic stirring at 580 rpm. After the treatment, the solid product was washed with deionized water by high-speed centrifugation (6000 rpm, 4 min) until the pH value of the upper liquid was higher than 6. The solid precipitated product was collected, transferred to a vacuum drying oven, and dried at 80 °C for 24 h to obtain Mo3C2T x Materials: Ti3C2T obtained in step (1) of Example 2 was mechanically mixed x Materials and Mo3C2T obtained in this step x Materials are composited (Ti3C2T x :Mo3C2T x =1:1 mass ratio), to obtain a catalyst carrier, denoted as B3.
[0059] (2) 1.10 g of basic cobalt carbonate, 0.43 g of ammonium metatungstate and 1.81 g of copper citrate were weighed and dissolved in deionized water to prepare a mixed aqueous solution, which was supersaturatedly impregnated onto 2 g of B3. After impregnation for 24 h, the excess solution was filtered off and the mixture was transferred to a vacuum drying oven and dried at 150 °C for 10 h. The mixture was then calcined in a muffle furnace at 650 °C for 4 h to obtain catalyst A5.
[0060] Example 6
[0061] (1) 2 g of Nb4AlC3 powder was slowly added to a mixed solution of 3.3 g of ammonium fluoride and 60 mL of hydrochloric acid (9 mol / L), and treated at 40 °C for 48 h under magnetic stirring at 600 rpm. After the treatment, the solid product was washed with deionized water by high-speed centrifugation (4500 rpm, 8 min) until the pH value of the upper liquid was higher than 6. The solid precipitated product was collected, transferred to a vacuum drying oven, and dried at 75 °C for 36 h to obtain Nb4C3T x Materials: Mo3C2T obtained in step (1) of Example 5 was mechanically mixed x Materials and Nb4C3T obtained in this step x Materials are composited (Nb4C3T x :Mo3C2T x =2:1 mass ratio), to obtain a catalyst carrier, denoted as B4.
[0062] (2) Weigh 1.69 g of ferric nitrate, dissolve it in deionized water to prepare an aqueous solution, impregnate an equal volume of it onto 4 g of B4, impregnate for 18 h, transfer it to a vacuum drying oven, and dry it at 130 °C for 10 h to obtain a catalyst precursor, recorded as K4; weigh 1.84 g of basic cobalt carbonate and 1.96 g of nickel oxalate, dissolve them in deionized water to prepare a mixed aqueous solution, impregnate K4 in a supersaturated manner, impregnate for 22 h, filter out the excess solution, transfer it to a vacuum drying oven, dry it at 120 °C for 12 h, and then calcine it at 600 °C in a muffle furnace for 8 h to obtain catalyst A6.
[0063] Depend on Figure 6 It can be seen that the Nb4C3T obtained in Example 6 x -Mo3C2T x The composite carrier has an accordion-like morphology.
[0064] Example 7
[0065] (1) The Ti3C2T3O4 obtained in step (1) of Example 2 was mixed by mechanical mixing. x Materials, Nb2CT obtained in step (1) of Example 3 x Materials and Example 5 Step (1) Mo3C2T x Materials and composites (Ti3C2T x :Nb2CT x :Mo3C2T x =3:1:2 mass ratio), to obtain a catalyst carrier, denoted as B5.
[0066] (2) Weigh 4.87 g of nickel nitrate, dissolve it in deionized water to prepare an aqueous solution, impregnate an equal volume of it onto 5 g of B5, impregnate for 10 h, transfer it to a vacuum drying oven, and dry it at 110 °C for 8 h to obtain a catalyst precursor, recorded as K5; weigh 1.45 g of ammonium tungstate and 4.22 g of ferric nitrate, dissolve it in deionized water to prepare a mixed aqueous solution, impregnate an equal volume of it onto K5, impregnate for 12 h, transfer it to a vacuum drying oven, dry it at 100 °C for 10 h, and then calcine it in a muffle furnace at 500 °C for 6 h to obtain catalyst A7.
[0067] Example 8
[0068] (1) The Ti3C2T3O4 obtained in step (1) of Example 2 was mixed by mechanical mixing. x Materials, Example 5 Step (1) Mo3C2T x Materials and Nb4C3T obtained in step (1) of Example 6 x Materials are composited (Ti3C2T x :Mo3C2T x :Nb4C3T x=6:4:3 mass ratio), to obtain a catalyst carrier, denoted as B6.
[0069] (2) 4.48 g of cobalt nitrate, 1.83 g of nickel carbonate and 0.87 g of copper citrate were weighed and dissolved in deionized water to prepare a mixed aqueous solution, which was supersaturatedly impregnated onto 5 g of B6. After impregnation for 36 h, the excess solution was filtered off and the catalyst was transferred to a vacuum drying oven and dried at 150 °C for 12 h. The catalyst was then calcined in a muffle furnace at 600 °C for 6 h to obtain catalyst A8.
[0070] Depend on Figure 7 It can be seen that the Ti3C2T obtained in Example 8 x -Mo3C2T x -Nb4C3T x The composite carrier has an accordion-like morphology.
[0071] Example 9
[0072] (1) The Ti3C2T3O4 obtained in step (1) of Example 2 was mixed by mechanical mixing. x Materials, Example 5 Step (1) Mo3C2T x Materials and Nb4C3T obtained in step (1) of Example 6 x Materials are composited (Ti3C2T x :Mo3C2T x :Nb4C3T x =7:2:4 mass ratio), to obtain a catalyst carrier, denoted as B7.
[0073] (2) Weigh 1.33 g of ammonium paramolybdate and 0.41 g of ammonium metatungstate, dissolve them in deionized water to prepare a mixed aqueous solution, supersaturate impregnate 5 g of B7, filter out excess solution after impregnation for 25 h, transfer it to a vacuum drying oven, and dry it at 130 °C for 14 h to obtain a catalyst precursor, recorded as K6; weigh 1.59 g of basic cobalt carbonate, dissolve it in deionized water to prepare an aqueous solution, impregnate an equal volume of K6, impregnate for 15 h, transfer it to a vacuum drying oven, dry it at 120 °C for 18 h, and then calcine it in a muffle furnace at 650 °C for 8 h to obtain catalyst A9.
[0074] Comparative Example 1
[0075] -Al2O3 was ordered from Dalian Haixin Chemical Co., Ltd. as a carrier. 1.94 g of cobalt nitrate and 3.24 g of nickel nitrate were weighed and dissolved in deionized water to prepare a mixed aqueous solution. An equal volume of the mixed aqueous solution was impregnated onto 2 g of -Al2O3 carrier. After impregnation for 20 h, the catalyst was transferred to a vacuum drying oven and dried at 120 °C for 14 h. The catalyst was then calcined at 550 °C in a muffle furnace for 6 h to obtain catalyst H1.
[0076] Performance Evaluation
[0077] According to the preparation method of the catalyst provided in the second aspect of the present invention, a series of bio-oil hydrodeoxygenation catalysts with layered MXenes as carriers can be obtained. The precursor MAX can be successfully obtained by liquid phase etching method using fluoride and hydrochloric acid reaction. From the XRD spectra of MAX and MXenes ( Figures 1 to 4 ) can be seen.
[0078] 1. Catalytic reaction performance evaluation
[0079] The catalyst performance evaluation was carried out in a fixed bed reactor. The catalysts prepared in Examples 1-9 and Comparative Example 1 were placed in a hydrogen atmosphere at 0.2 MPa and a gas space velocity of 1900 h -1 , pre-reduction treatment at 400 °C for 6 h, then, the reaction temperature was 300 °C, the hydrogen pressure was 3.0 MPa, and the gas space velocity was 1900 h -1 Under the reaction conditions of hydrogen / oil volume ratio of 900, stearic acid (model compound) was used as the reaction raw material for the hydrodeoxygenation reaction. The catalytic reaction performance results are shown in Table 1.
[0080] Table 1. Catalytic performance results of Examples 1-9 and Comparative Example 1 using stearic acid as raw material
[0081]
[0082] As shown in Table 1, compared with Comparative Example 1, Examples 1 and 2 using a MXenes as a carrier exhibited better hydrodeoxygenation performance and inhibited side reactions such as decarboxylation and decarbonylation, which reflects the advantages of layered carriers in improving catalytic performance. x The hydrodeoxygenation effect of Example 2 is better, which is due to the Ti3C2T x The C / Ti value in the material is higher than Ti2CT x The electronegativity of carbon atoms is relatively large, which can cause the electron cloud in the transition metal (Ti) to shift. When there are more carbon atoms around the transition metal, the degree of shift increases, which is beneficial to improve the adsorption of hydrogen and raw materials by the transition metal site, thereby achieving the improvement of the hydrogenation and deoxygenation catalytic performance. On this basis, Ti2CT x Materials and Nb2CT x When the material is prepared into a composite carrier, the hydrodeoxygenation catalytic performance can also be effectively improved (Example 3); x Material composite to Ti3C2T x When using Ti3C2T xCompared with the material (Example 2), the catalytic performance is not significantly improved; further, Mo3C2T x Materials and Ti3C2T x When the material is prepared into a composite carrier (Example 5), it can show better performance than Ti3C2T x The catalytic performance of the material alone as a carrier (Example 2); similarly, Nb4C3T x Materials and Mo3C2T x When the materials are composited (Example 6), they can also show catalytic performance better than that of Example 5. In addition, in the three MXenes composite supports, the hydrodeoxygenation performance of each catalyst still reflects this rule. That is, when the C / M (M=Ti, Nb, Mo) value in the composite support is equal, the hydrodeoxygenation catalytic performance can be improved; as the C / M (M=Ti, Nb, Mo) value in the composite support increases, the catalytic performance also tends to gradually improve.
[0083] Therefore, in the examples listed, the catalyst A8 obtained in Example 8 has a better catalytic effect on the hydrogenation deoxygenation reaction of stearic acid, which is reflected in the high conversion rate of stearic acid and the high catalytic effect of catalyst A8 on nC 18 The selectivity is the highest for nC 17 、nC 16 The selectivity is low, indicating that the catalyst can make stearic acid more inclined to undergo hydrogenation and deoxygenation reaction, which not only improves the hydrogenation depth but also ensures the utilization efficiency of carbon atoms.
[0084] The GC spectra of the catalyst A8 obtained in Example 8 for the hydrogenation deoxygenation reaction product (b) of stearic acid and the raw material stearic acid (a) are as follows: Figure 8 As shown in the figure, it can be seen that in the product distribution (b), through qualitative analysis, the product nC appears at retention times of 6.07 min, 4.45 min, and 3.33 min, respectively. 18 、nC 17 、nC 16 Peak (with mixed standard solution nC 18 ~ 16 The peak of raw material stearic acid did not appear at the retention time of 16.54 min, indicating that the raw material stearic acid was completely converted during the catalytic hydrodeoxygenation reaction. Through quantitative analysis, it can be seen that nC 18 、nC 17 、nC 16 The content ratio is about 7:2:1.
[0085] 2. Catalyst stability performance test
[0086] Catalyst A8 was loaded in a fixed bed reactor and heated under a hydrogen atmosphere at 0.2 MPa and a gas space velocity of 2000 h -1, pre-reduction treatment at 400 °C for 6 h, then, the reaction temperature was 400 °C, the hydrogen pressure was 3.0 MPa, and the gas space velocity was 2000 h -1 Under the reaction conditions of 1000 hydrogen / oil volume ratio, cottonseed oil was used as the reaction raw material for hydrodeoxygenation reaction, and the reaction lasted for 600 h. The main components of cottonseed oil are shown in Table 2. Under this condition, the catalyst stability test results are shown in Fig. 9 shown.
[0087] Table 2. Composition of cottonseed oil
[0088] Fatty acid type Abbreviation Content / wt.% Palmitic acid C16:0 18.66 Palmitoleic acid C16:1 2.99 Heptadecanoic acid C17:0 15.56 Stearic acid C18:0 2.78 Elaidic Acid C18:1-trans 0.61 Oleic acid C18:1-cis 3.24 Linoleic acid C18:2 2.12 Gamma-linolenic acid C18:3n6 51.28 α-linolenic acid C18:3n3 2.75
[0089] Depend on Fig. 9 It can be seen that the catalyst A8 obtained in Example 8 has a significant effect on the hydrodeoxygenation of the main product nC 18 、nC 17 、nC 16 There is still a high selectivity, indicating that the catalyst has good stability, long service life and is not easy to deactivate. It also shows that the composite carrier can still enable the catalyst to maintain good catalytic activity for a long time under high temperature conditions, effectively solving the shortcomings of poor stability and low catalytic activity of the existing technology for preparing bio-oil hydrodeoxygenation catalysts, providing a guarantee for industrial development and utilization.
Claims
1. A bio-oil hydrodeoxygenation catalyst, characterized in that: Including hydrogenation active metals, hydrogenation auxiliary metals and MXenes material carrier Ti3C2T x -Mo3C2T x -Nb4C3T x ; The hydrogenation active metals are Co and Ni; the hydrogenation auxiliary metal is Cu; The preparation method of the bio-oil hydrodeoxygenation catalyst comprises the following steps: (1) Slowly add Ti3AlC2, Mo3AlC2 or Nb4AlC3 powder to a hydrochloric acid solution containing a fluorine compound according to a molar ratio of Ti3AlC2, Mo3AlC2 or Nb4AlC3 to fluoride ions of 1:7 to 1:30; etch at a speed of 200 to 1200 rpm and a temperature of 0 to 60 °C for 2 to 72 h; (2) The product obtained in step (1) was separated into solid and liquid, washed with deionized water until the pH value was greater than 6, and the obtained solid precipitate was vacuum dried at 55-100°C for 12-48 h to obtain Ti3C2T x 、Mo3C2T x or Nb4C3T x ; By mass ratio Ti3C2T x :Mo3C2T x :Nb4C3T x =6:4:3, the obtained Ti3C2T x 、Mo3C2T x and Nb4C3T x The materials are compounded to obtain a MXenes material carrier; (3) Weigh 4.48 g of cobalt nitrate, 1.83 g of nickel carbonate and 0.87 g of copper citrate, dissolve them in deionized water to prepare a mixed aqueous solution, and supersaturate impregnate 5 g of the MXenes material carrier. After impregnation for 36 h, filter out the excess solution, transfer it to a vacuum drying oven, dry it at 150 °C for 12 h, and then calcine it at 600 °C in a muffle furnace for 6 h to obtain a bio-oil hydrodeoxygenation catalyst.
2. The method for preparing the bio-oil hydrodeoxygenation catalyst according to claim 1, characterized in that: The following steps are involved: (1) Slowly add Ti3AlC2, Mo3AlC2 or Nb4AlC3 powder to a hydrochloric acid solution containing a fluorine compound according to a molar ratio of Ti3AlC2, Mo3AlC2 or Nb4AlC3 to fluoride ions of 1:7 to 1:30; etch at a speed of 200 to 1200 rpm and a temperature of 0 to 60 °C for 2 to 72 h; (2) The product obtained in step (1) was separated into solid and liquid, washed with deionized water until the pH value was greater than 6, and the obtained solid precipitate was vacuum dried at 55-100°C for 12-48 h to obtain Ti3C2T x 、Mo3C2T x or Nb4C3T x ; By mass ratio Ti3C2T x :Mo3C2T x :Nb4C3T x =6:4:3, the obtained Ti3C2T x 、Mo3C2T x and Nb4C3T x The materials are compounded to obtain a MXenes material carrier; (3) Weigh 4.48 g of cobalt nitrate, 1.83 g of nickel carbonate and 0.87 g of copper citrate, dissolve them in deionized water to prepare a mixed aqueous solution, and supersaturate impregnate 5 g of the MXenes material carrier. After impregnation for 36 h, filter out the excess solution, transfer it to a vacuum drying oven, dry it at 150 °C for 12 h, and then calcine it at 600 °C in a muffle furnace for 6 h to obtain a bio-oil hydrodeoxygenation catalyst.
3. The preparation method according to claim 2, characterized in that: The fluorine compound includes one or more of lithium fluoride, sodium fluoride, potassium fluoride, and ammonium fluoride; the concentration of the hydrochloric acid is 6-15 mol / L.
4. The use of the bio-oil hydrodeoxygenation catalyst according to claim 1, characterized in that: Used for the hydrodeoxygenation reaction of bio-oils.
5. A method for using the bio-oil hydrodeoxygenation catalyst according to claim 1 for hydrodeoxygenation reaction, characterized in that: The process comprises using biomass oil as raw material, reducing it at 200-550 °C for 2-12 h in a hydrogen atmosphere, with a reduction pressure of normal pressure to 3.0 MPa and a gas space velocity of 1000-10000 h -1 The bio-oil hydrodeoxygenation catalyst is placed in a fixed bed reactor to perform a hydrodeoxygenation reaction.
